2009
DOI: 10.1051/0004-6361/200810801
|View full text |Cite
|
Sign up to set email alerts
|

The diverse X-ray properties of four truly isolated elliptical galaxies: NGC 2954, NGC 6172, NGC 7052, and NGC 7785

Abstract: Aims. We investigate the X-ray properties of four isolated elliptical galaxies, selected from the Updated Zwicky Catalog according to strict isolation criteria. Isolated galaxies are not influenced by the group/cluster environment, and their X-ray emission can be studied independently of the often overwhelming contribution of the hot intergalactic medium. They are therefore suited to studying the X-ray characteristics relative to their intrinsic properties. Methods. We analyzed our own XMM-Newton and archival … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 108 publications
2
39
0
Order By: Relevance
“…The net radial surface brightness profiles, centered at the X-ray peak of the EPIC-pn data in the 0.5-2.0 keV energy band, are well reproduced by a β-model whose best-fit values of r c and β are given in Table 1 (see also Memola et al 2009). …”
Section: X-ray Observationsmentioning
confidence: 71%
See 2 more Smart Citations
“…The net radial surface brightness profiles, centered at the X-ray peak of the EPIC-pn data in the 0.5-2.0 keV energy band, are well reproduced by a β-model whose best-fit values of r c and β are given in Table 1 (see also Memola et al 2009). …”
Section: X-ray Observationsmentioning
confidence: 71%
“…Note that NGC 7052 and NGC 7785, with L X < 2 × 10 41 erg s −1 , and M TOT < 2 × 10 12 M (see Table 3 in Memola et al 2009) do not appear to be fossil groups (e.g., Jones et al 2003;Pompei et al 2007) because they do not show their physical properties. Fossil groups (e.g., NGC 1132, Mulchaey & Zabludoff 1999) have, indeed, so far been observed with larger masses 10 13 −10 14 M , and X-ray luminosity >10 42 erg s −1 (see Fig.…”
Section: The Isolated Ellipticals Ngc 7052 and Ngc 7785mentioning
confidence: 99%
See 1 more Smart Citation
“…However, successive generations of X-ray telescopes with improved sensitivity, larger effective areas, and superior spatial resolution are now beginning to allow a more in-depth study of the hotgas component in unprecedented detail, which in turn sheds new light on the formation history of galaxies. Using the excellent angular resolution of the Chandra X-ray telescope, studies are directly detecting and isolating the X-ray emission from stellar processes such as the low-mass X-ray binary population that have plagued the previous generation of X-ray telescopes, particularly in the low stellar mass regime (e.g., Sivakoff et al 2004;Boroson et al 2011;Lehmer et al 2014), as well as exploring the X-ray halos in early-type galaxies as a function of cosmic time (e.g., Lehmer et al 2007;Civano et al 2014;Paggi et al 2015) and probing the thermal gas content (e.g., Diehl & Statler 2007;Jeltema et al 2008;Memola et al 2009;Bogdán et al 2012aBogdán et al , 2012bKim & Fabbiano 2013Su et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The properties of isolated early-type galaxies provide a probe of whether environmental effects can account for the bulk of the scatter in L X /LB . Memola et al (2009) assembled LX -LB data for 27 isolated ellipticals, and found a good deal of scatter. However, excluding probable 'fossil groups' (Ponman et al (1994)) and upper limits, the remaining sample is small.…”
Section: Sources Of Scatter In L X -L Optmentioning
confidence: 99%